A Low-Dose 4F-PCC Protocol for DOAC-Associated Intracranial Hemorrhage. (November 2020) - Berger, Karen; Santibañez, Melissa; Lin, Lina; Lesch, Christine A.
Purpose: Current guidelines favor 4F-PCC over plasma for reversal of warfarin. Uncertainty remains on the hemostatic effectiveness and thrombotic risk of 4F-PCC for direct-acting oral anticoagulants (DOACs), particularly in patients with intracranial hemorrhage (ICH). This study sought to evaluate the effectiveness and safety of a lower dose protocol of 25 units/kg 4F-PCC for the management of DOAC-associated ICH in a real-world setting. Materials and Methods: This was a retrospective study of adult patients who received at least one dose of 4F-PCC from March 2014 to December 2015 for DOAC-associated ICH. The primary outcome was hemostatic effectiveness within 24 hours. The secondary outcome was thromboembolic events within 14 days. Results: Twenty-two patients received 4F-PCC for DOAC-associated ICH and were included in the analysis. Hemostasis was evaluable in 19 patients with post-4F-PCC imaging available and occurred in 18/19 (94.7%) patients. Thromboembolism occurred in 2 out of 22 patients (9.1%). Conclusions: The use of a lower dose protocol of 25 units/kg of 4F-PCC resulted in high rates of hemostasis in patients with DOAC-associated ICH. Two patients developed thrombotic events within 14 days of 4F-PCC administration.